The Effect of Anemia on Prognostic in Non-Small Cell Lung Cancer Patients Receiving Platinum-Based Chemotherapy - Kartikasari, Ulfah; Pratiwi, Suryanti Dwi; Astuti, Tri Wahju; Setijowati, Nanik (Jurnal Respirasi, 2024)
Introduction: Lung cancer has the highest incidence and mortality rate, which contributes to approximately 2.2 million cancer cases (11.4%) of total cancers worldwide. More than 70% of lung cancer cases present in the late, non-operable stage. Anemia is one of the conditions that could precipitate cancers and affect the patient's clinical presentation, including tissue oxygenation, organ function, and quality of life. It could also increase the risk of bleeding, post-operative mortality, and iron absorption rate in the case of ineffective erythropoiesis. All of these could affect the prognostic factor of the cancer. This study aimed to evaluate the effect of the severity of anemia on overall survival (OS) and progression-free survival (PFS) in non-small cell lung cancer (NSCLC) patients treated with platinum-based chemotherapy. Methods: This was a retrospective cohort study involving 80 subjects of NSCLC patients treated with platinum-based chemotherapy from January 2018 to December 2020. Subjects were divided into two groups (39 patients in the normal group and 41 patients in the anemia group). Results: The mean pre-treatment hemoglobin (Hb) was 10.55 ± 1.25 g/dL in NSCLC patients with anemia. The bone metastasis, OS, and PFS values of the normal and anemia groups were significant (p = 0.008; p = 0.002; p = 0.27). Anemia was significantly related to OS (r = 0.146, p = 0.000) and PFS (r = 0.264, p = 0.000) in NSCLC patients treated with platinum-based chemotherapy. Conclusion: Higher severity of anemia can reduce OS and PFS in NSCLC patients treated with platinum-based chemotherapy.